Design Innovative Solution Model for Banking Specific Financing in Rice Commodity Agribusiness in South Sulawesi - Z Zulkifli; Sri Mardiyati; H Hamzah; Abubakar Idhan; S Suhartina (Fapetrik-UMPAR, 2021)
The long history of agricultural credit schemes in Indonesia as the track record revealed was distinctively devided into (i) Pre-Social Development (1964), (ii) Socio-national Development and Collaboration (1965-1970), Completed Social Development (1970-1984), (iv) Farm Credit (1985-1999), (v) Food Security Credit (2000), (vi) Energy and Food Security Credit (2007), (vii) People Business Credit (2007 – up to recent time). Nevertheless, up to these days non of the agrcultural financing schemes that are consistantly specified to rice product commodity development. This research aimed at 1. Analyzing the obstacles hindering the distribution of the rice commodity agribusiness financing scheme specifically viewed from the collaborative side of financial institution and rice agribusiness farmers, 2. Compehensively analyzing the procedural system for distributing financing schemes implemented to rice agribusiness farmers mainly viewed from the aspects of (i) credit interest rate, (ii) credit limit, (iii) credit recipients, (iv) credit disbursement, (v) credit refund, (vi) credit refund time, and (vii) credit collateral 3. Designing an innovative solution model for banking specific financing reserved to rice commodity agribusiness farmers. The findings of this collaborative research were as follow: (1) obstcales hindering banking institutions from distributing fund to rice farmers were the credit allocation policy itself that is relatively centralized, whereas from the side of agribusiness doers seemed to derived from the weakness of finance administration system as well as the less of bankable collasteral values; (2) Financing schemes disbursement procedural system implemented by credit channelling agencies such as BRI, BNI, and other local banks did not meet with the needs and expectation of agribusiness doers, sophisticated, and too bureaucratic as well, (3) the innovative solution model for bank financing specified to rice commodity agribusiness resulted of this collaborative research was called Rice Agribusiness Credit Scheme (RACS) in which local government squeeze as both coordinator and coach.